2006
DOI: 10.1096/fj.05-4044lsf
|View full text |Cite
|
Sign up to set email alerts
|

N6‐isopentenyladenosine arrests tumor cell proliferation by inhibiting farnesyl diphosphate synthase and protein prenylation

Abstract: The physiological effects of a variety of N6-substituted adenine and adenosine derivatives called cytokinins have been documented in plants, but information on their occurrence and function in other biological system is limited. Here we investigated the anti-proliferative effect of N6-isopentenyladenosine (i6A), an adenosine and isoprenoid derivative, in a thyroid cell system, FRTL-5 wild-type, and K-ras transformed KiMol cells. Addition of i6A to FRTL-5 cells caused a dose-dependent arrest of the G0-G1 cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
103
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(111 citation statements)
references
References 35 publications
7
103
1
Order By: Relevance
“…Despite abundant evidence of the in vitro antitumour activity of i 6 A, this molecule has only a slight effect, if any, on tumour growth in rodents, 12 as well as in a pilot clinical trial. 13 The reason(s) for this discrepancy may rest in a rapid catabolism 14 or short plasma half-life of i 6 A, in analogy to other nucleosides.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Despite abundant evidence of the in vitro antitumour activity of i 6 A, this molecule has only a slight effect, if any, on tumour growth in rodents, 12 as well as in a pilot clinical trial. 13 The reason(s) for this discrepancy may rest in a rapid catabolism 14 or short plasma half-life of i 6 A, in analogy to other nucleosides.…”
mentioning
confidence: 98%
“…As a tRNA modification, i 6 A contributes to reading frame maintenance, 3 and the lack of i 6 A in selenocysteine tRNA can affect synthesis of selenoproteins. 4 We previously showed that i 6 A exerts potent in vitro antitumour activity on human epithelial cancer cell lines derived from different types of tumours.…”
mentioning
confidence: 99%
See 3 more Smart Citations